Exploring Virtual Reflective Learning Experiences in Higher Education - Anca Luștrea; Melinda Dincă; Mariana Crașovan; Atalia Onițiu; Dan Lucheș; Håkon Fyhn; Jens Røyrvik (Revista de Știinţe Educaţiei, 2023)
As a result of the COVID-19 pandemic, formal education underwent a period of rapid transformation. Beyond this period, the virtual learning environment proposed a reevaluation of curriculum design and didactic strategies. The Classroom Laboratory NTNU-WUT Joint Course (CL) was introduced as a novel learning experience for students at West University of Timisoara (WUT) and the Norwegian University of Science and Technology (NTNU). This experimental course was proposed as part of the Romania-Norway collaboration and incorporates Virtual Project Based Learning (VPBL) in crosscultural and cross-disciplinary online learning groups. This study aims to describe the learning experiences of Romanian students enrolled at WUT in the CL course during the 2021–2022 academic year. In a quasi-experimental design, 24 Romanian students participated in a seven-week transversal CL course, collaborating with Norwegian peers to develop a solution for a social problem. ••Students made significant gains in all three dimensions targeted by VPBL: skill development, self-regulation of learning, and group interactions in the online environment. In addition, the learning of students was compared based on the field of science they are pursuing (STEM and non-STEM). The results indicate that students enrolled in STEM disciplines demonstrated greater benefits from this instructional approach, as evident in their progress across the three dimensions of PBL. The qualitative analysis of the students' journals reveals a positive learning experience in terms of knowledge acquisition, skill development, and affective engagement. In conclusion, CL and VBPL are valid strategies for online university-level instruction.